Rapid ichthyological inventory of lower Pachitea Basin, Peru - Palacios, Vanessa E. (2008)
This paper reports on the fish diversity in the lower Pachitea River basin. In July 2005 a rapid inventory in 31 field stattions (14 rivers, 13 streams and 4 lagoons) was conducted. The area was located between Honoria (456195E, 8830474N) and Zungaro (486747E, 8965585N) between the departments of Huanuco and Ucayali. Fishes were caught using seines (4 mm, mesh), and 3967 were captured. 116 species, 25 families and eight orders were identified. Characiforms (59%), Siluriforms (22%) y Perciforms (12%) had the greatest richness. Commercial fishes as Cichla monoculus, Prochilodus nigricans, Salminus hilari, Hoplias malabaricus, Liposarcus sp., Plagioscion squomosissimus and ornamentals as Heros severus, Corydoras stenocephalus, Mesonauta festivus, Pyrrhulina brevis were fished too. Analysis of the richness by types of habitats showed that the streams were more diverses (64 species) than rivers (54) and lagoons (45). The rivers (1934 individuals) and streams (1745) were the habitat with higher abundances followed by and lagoons (253).